Do athletes have a right to access data in their Athlete Biological Passport?. Issue 5 (20th April 2018) - Devriendt, Thijs; Chokoshvili, Davit; Favaretto, Maddalena; Borry, Pascal
Abstract: The Athlete Biological Passport (ABP) refers to the collection of data related to an individual athlete. The ABP contains the Haematological Module and the Steroidal Module, which are used for the longitudinal monitoring of variables in blood and urine, respectively. Based on changes in these variables, a statistical model detects outliers which indicate doping use and guide further targeted testing of the athlete. Presently, athletes can access their data of the Haematological Module in the Anti‐Doping Administration and Management System (ADAMS). However, granting athletes access to this data has been a matter of debate within the anti‐doping community. This article investigates whether an athlete has a right to access the contents of their ABP profile. We approached this discussion by comparing the nature of ABP data with that of forensic and medical data and touched on important concerns with ABP data disclosure to athletes such as potentially allowing for the development of alternative doping techniques to circumvent detection; and making athletes vulnerable to pressure by the media to publicly release their data. Furthermore, given that ABP data may contain medically relevant information that can be used to diagnose disease, athletes may over‐interpret its medical significance and wrongly see it as a free health check. We argue that safeguarding the integrity of the ABP system must be seen as the most essential element and thus a departure from immediate data disclosure is necessary. Two different strategies for delayed data disclosure are proposed which diminish the chances of ABP data being misused to refine doping techniques. Abstract : Disclosure of ABP data to athletes might undermine the integrity of the anti‐doping system by promoting alternative doping strategies. Athletes might be pressured to release this data, potentially leading to false accusations. Simultaneously, abnormal findings in ABP data could indicate underlying pathologies and thus be valuable for medical diagnostics.